The relationship between acute:chronic workload ratio and injury risk during the in-season in elite Japanese rugby union players - Yamamoto, H.; Takemura, M.; Fukuhara, K.; Arijit, B.; Kurita, K.; Tachibana, M.; Shiota, S.; Tsujita, J.; Hojo, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Absolute weekly workloads (1-4 weekly) and acute workloads relative to chronic workloads have been investigated. However, the association between workload and injury may vary from sport to sport and competition league. Therefore, the purpose of this study was to investigate the association between workload and injuries in elite Japanese rugby union players.